The Aesthetics of Surakarta Palace’s Karawitan According to Serat Sri Karongron - Joko Daryanto; Rustopo Rustopo; Bambang Sunarto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2020)
Aesthetics is an observation of beauty, values, and judgments that view human works from the perspective of whether they are beautiful and not—Serat Sri Karongron by R. Ng. Purbadipura was written during the reign of Paku Buwana X, releasing a pulse of musical life in the Surakarta Palace, which implies the artistic content of the Surakarta Palace’s karawitan. Serat Sri Karongron explicitly mentions the atmosphere of the Seger sumyah karawitan feeling. The phrase Seger sumyah can be interpreted as something that can make someone feel happy because Seger sumyah refers to an excellent or delicious taste. Purbadipura notes that Seger sumyah refers to the gobyog karawitan presentation at the Surakarta Palace. On the other hand, Purbadipura reported that the gobyog karawitan presentation still refers to the karawitan presentation with three parameters of tan sora swaranira, rampak-rempeg, and sajanturing ringgit. The aesthetics of the Seger sumyah karawitan, which refers to karawitan composition with the nuances of gobyog, had a chance to live and develop during the reign of Paku Buwana X.